Inhibition conduction loss for distinct improvement of energy storage density over a broad temperature range in polyetherimide-based composite films. (16th January 2023) - Chen, Hanxi; Pan, Zhongbin; Cheng, Yu; Ding, Xiangping; Li, Zhicheng; Fan, Xu; Liu, Jinjun; Li, Peng; Yu, Jinhong; Zhai, Jiwei
Abstract: The exploration of high-energy-density polymer dielectrics that can operate stably under high temperatures is of great significance in order to meet the growing needs for modern high-power electronics. However, the drastically deteriorated capacitive performances brought by the inevitable conduction loss at elevated temperature grievously hinder their application in extreme circumstances. Herein, a class of sandwich-structured dielectric nanocomposites capitalizing on binary wide-bandgap nanofillers is reported. The synergy of wide bandgap Al2 O3 nanoparticles and hydroxyl-modified BNNSs can build higher interfacial barrier to efficiently depress the thermionic charge injection and carrier transport in dielectrics, yielding a substantially inhibited electrical conduction of the composites under elevated temperature. Indeed, the resulting sandwich-structured polymer composites deliver first-class-level discharged energy density ( U d ) of ∼2.23 J/cm 3 with efficiency ( η ) > 90% even under the ultra-high temperature of 200 °C, which is by far the current free-standing high-temperature dielectric polymer and polymer-based composites reported to date. Together with remarkable dielectric stability over a wide temperature and frequency range and outstanding cyclability, this contribution puts forward an efficient approach to groping for scalable high-temperature dielectric polymer nanocomposites for advanced electrical energy storage. Graphical abstract: Image 1 Highlights: Wide-bandgap nanofillers could hinder thermionic charge injection and carrier transport. Excellent discharged energy density of ∼2.23 J/cm 3 and conspicuous efficiency of ∼90% even at 200 °C are attained. The composites exhibit an outstanding reliability of energy storage performance under continuous cycling.